2012
DOI: 10.1155/2012/762825
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress, Tumor Microenvironment, and Metabolic Reprogramming: A Diabolic Liaison

Abstract: Conversely to normal cells, where deregulated oxidative stress drives the activation of death pathways, malignant cells exploit oxidative milieu for its advantage. Cancer cells are located in a very complex microenvironment together with stromal components that participate to enhance oxidative stress to promote tumor progression. Indeed, convincing experimental and clinical evidence underline the key role of oxidative stress in several tumor aspects thus affecting several characteristics of cancer cells. Oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
220
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(226 citation statements)
references
References 92 publications
5
220
0
1
Order By: Relevance
“…In addition, hypoxia through the impairment of complex III (cytochrome b oxidoreductase) of the mitochondrial respiratory chain and the activity of NADPH oxidase of macrophages play important roles in aggregate ROS and the intrinsic oxidative stress in tumors. Thus, the hypoxia participates in the induction of tumor angiogenesis and promotes cancer (Barrera, 2012;Fiaschi and Chiarugi, 2012;Sosa et al, 2013). Studies have shown that oxidative stress affects several signaling pathways associated with cell proliferation (Soliman et al, 2014).…”
Section: Oxidative Stress and Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, hypoxia through the impairment of complex III (cytochrome b oxidoreductase) of the mitochondrial respiratory chain and the activity of NADPH oxidase of macrophages play important roles in aggregate ROS and the intrinsic oxidative stress in tumors. Thus, the hypoxia participates in the induction of tumor angiogenesis and promotes cancer (Barrera, 2012;Fiaschi and Chiarugi, 2012;Sosa et al, 2013). Studies have shown that oxidative stress affects several signaling pathways associated with cell proliferation (Soliman et al, 2014).…”
Section: Oxidative Stress and Cancermentioning
confidence: 99%
“…Hence, the activity of the JNK pathway plays an important management role in apoptosis. Some studies indicate that the inhibition of JNK also causes changes in the cell aging process and correspondingly increases the production of free radicals in mitochondria and causes oxidative damage to DNA in MCF-7 breast cancer cells (Martindale and Holbrook, 2002;Schramek et al, 2011;Fiaschi and Chiarugi, 2012;Raj et al, 2012). P66sch proteins also persuade ROS production by inducing the expression of prolin oxidase.…”
Section: Oxidative Stress and Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…49,50 We measured the change of total area covered by HuH7 using phase contrast images of the co-culture chip, which was processed by ImageJ software (detailed procedure illustrated in Figure S3, supplementary material). 52 It was observed that the coverage of tumor cells increased significantly after day 4 ( Figure 6(a)).…”
Section: Resultsmentioning
confidence: 99%
“…The transcription factors HIF-1 and HIF-2 play also a crucial role in the metabolic reprogramming of both CAFs and tumor cells. Although their role remains controversial under hypoxia, clear evidence now exist indicating that ROS stabilize the HIF proteins under normoxic conditions through modulation of PHD enzyme activity [40][41][42][43][44]. Fiaschi and Chiarugi [43] have shown that accumulation of ROS and HIF stabilization in CAFs result also from the downregulation of SIRT3, a mitochondrial NAD-dependent deacetylase.…”
Section: Ros and Hif-1 Involvement In Cancer Metabolismmentioning
confidence: 99%